Comparative reducing and carbohydrate enzyme inhibitory activities of the root, leaf, and seed of Picralima nitida - Erwin Osiele Onyekachukwu; Aishat Mary Osagie; Sylvia Oghogho Omage; Kingsley Omage; Marshall Arebojie Azeke (Phytomedicine Plus)
Background: The ethnomedicinal uses of Picralima nitida is partly due to its antidiabetic properties. Purpose: In this study, the antioxidant and total reducing power, as well as the carbohydrate hydrolysing enzymes’ inhibition potentials of the root, leaf, and seed of P. nitida were compared. Methods: The antioxidant reducing power of P. nitida as well as its ability to inhibit selected enzymes of carbohydrate hydrolysis were evaluated using standard experimental methods. Results: Methanol extract of P. nitida leaves exhibited the strongest reducing power (653.52 mgASC/g) followed by the seed extract (620.11 mgASC/g). The free radical scavenging powers of the extracts were concentration dependent. P. nitida seed extract exhibited the highest scavenging ability (IC50 = 190.7 µg/ml) as compared to the root extract (IC50 = 470.40 µg/ml) and leaf extract (IC50 = 560.65 µg/ml). However, the seed extract had the highest ABTS radical scavenging ability (IC50 = 174.02 ± 0.75 µg/ml) in comparison with the root extract (IC50 = 181.83 ± 1.01 µg/ml) and leaf extract (IC50 = 279.87 ± 1.39 µg/ml). Alpha-amylase and alpha-glucosidase inhibitory properties of the extracts increased steadily with increasing concentration, as that of glibenclamide. The methanolic extract of P. nitida seed had the highest inhibitory activity (95.70 %) as compared to that of the root (92.39 %) and leaf (83.58 %) extracts. Conclusion: P. nitida show strong reducing as well as enzyme inhibitory properties which are concentration dependent and compares favourably with glibenclamide. Comparatively, the methanolic extract of the leaf of P. nitida exhibited the highest reducing power and inhibition of α-amylase, while the methanolic seed extract exhibited the highest ability to fight free radicals and inhibit the activity of α-glucosidase.